2021
DOI: 10.3389/fmicb.2021.781138
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Characterization of a High-Efficiency Chitosanase From Bacillus mojavensis SY1 Suitable for Production of Chitosan Oligosaccharides

Abstract: Chitosanase plays an important role in enzymatic production of chitosan oligosaccharides (COSs). The present study describes the gene cloning and high-level expression of a high-efficiency chitosanase from Bacillus mojavensis SY1 (CsnBm). The gene encoding CsnBm was obtained by homologous cloning, ligated to pPICZαA, and transformed into Pichia pastoris X33. A recombinant strain designated X33-C3 with the highest activity was isolated from 120 recombinant colonies. The maximum activity and total protein concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…The expression level of chitosanases from Mitsuaria sp., Streptomyces sp. N174, B. amyloliquefaciens, A. fumigatus CJ22-326, and Bacillus mojavensis SY1 (B. mojavensis SY1) are almost 1.6, 8.5, 4.5, 3.1, and 3.8 g/l, respectively (Peng et al, 2013;Ding et al, 2019;Luo et al, 2020;Zhou et al, 2020;Wang J. R. et al, 2021). Similar with previous works, the production of ShCsn46 was 3.91 g/l and the recombinant ShCsn46 was the main protein of supernatant (Figure 3B).…”
Section: Overexpression Of Shcsn46 In Pichia Pastoris X33supporting
confidence: 85%
See 3 more Smart Citations
“…The expression level of chitosanases from Mitsuaria sp., Streptomyces sp. N174, B. amyloliquefaciens, A. fumigatus CJ22-326, and Bacillus mojavensis SY1 (B. mojavensis SY1) are almost 1.6, 8.5, 4.5, 3.1, and 3.8 g/l, respectively (Peng et al, 2013;Ding et al, 2019;Luo et al, 2020;Zhou et al, 2020;Wang J. R. et al, 2021). Similar with previous works, the production of ShCsn46 was 3.91 g/l and the recombinant ShCsn46 was the main protein of supernatant (Figure 3B).…”
Section: Overexpression Of Shcsn46 In Pichia Pastoris X33supporting
confidence: 85%
“…Meanwhile, the hydrolytic pattern of ShCsn46 is similar to many previous reported chitosanases. Most of the chitosanases from GH46 display endo-type property and without activity toward (GlcN) 2 and (GlcN) 3 (Jiang et al, 2012;Luo et al, 2020;Sun et al, 2020;Zhou et al, 2020;Wang J. R. et al, 2021). Furthermore, the hydrolytic process of (GlcN) 6 revealed that ShCsn46 may have two binding and cutting modes, which are "4 + 2" and "3 + 3" splitting mode, respectively (Figure 5F).…”
Section: Hydrolytic Pattern Of Shcsn46mentioning
confidence: 99%
See 2 more Smart Citations
“…As a mature expression host, B. subtilis is widely used to produce a variety of enzymes and proteins due to its extracellular secretion of target recombinant protein (Song et al, 2015;Cui et al, 2018). Compared with E. coli and Pichia pastoris, B. subtilis exhibits several advantages such as ease of genetic manipulation, being classified as generally recognized as safe (GRAS) and easy cultivation, and short fermentation time (Gu et al, 2018;Wang et al, 2021b). Recently, several proteases are heterologously expressed in B. subtilis including alkaline and neutral proteases from Bacillus clausii TCCC1004, Geobacillus stearothermophilus (G. stearothermophilus), Bacillus licheniformis, and Idiomarina sp.…”
Section: Introductionmentioning
confidence: 99%